Effect of feeding dry-rolled corn or whole shelled corn during the finishing phase on growth performance and carcass characteristics. Issue 1 (15th December 2020) - Freitas, Tiago B; Felix, Tara L; Clark, Chris; Fluharty, Francis L; Relling, Alejandro E
Abstract: The objectives of this trial were to evaluate the effect of corn processing during the finishing phase on feedlot cattle performance and carcass characteristics. We hypothesized that steers fed dry-rolled corn would have better feed efficiency (less feed necessary to the same amount of gain) than steers fed whole shelled corn. Ninety-five backgrounded Angus-cross cattle (initial body weight [BW] = 263 ± 9.8 kg) were used in a randomized complete block design in a feedlot setting. Cattle were divided in to 3 blocks: heifers (n = 31, 4 pens; initial BW = 267 ± 1.3 kg), light steers (n = 32, 4 pens; initial BW = 253 ± 1.3 kg), and heavy steers (n = 32, 4 pens; initial BW = 279 ± 1.4 kg). Diets contained 70% corn (experimental treatment), 15% dried distiller's grains with solubles, 7% grass hay, and 8% supplement, on a dry matter basis. Cattle were fed for 217, 224, and 231 ± 8 d for the heifer, heavy steer, and light steer blocks, respectively. Two pens within each block were randomly assigned to one of the following treatments: (1) dry-rolled corn (DRC) or (2) whole-shelled corn (WSC). Animal growth performance and carcass characteristics were analyzed using the MIXED procedure of SAS, including the fixed effect of treatment. Pen and block were included as random effects. Carcass characteristics USDA Yield Grade and Quality Grade distributions were compared using the GLIMMIX procedure of using the same model than the growth performance data. Data are presented as LSMeans. Cattle fed DRC had greater average daily gain (ADG; P = 0.02) and final BW ( P < 0.01) when compared with cattle fed WSC. Even though ADG was greater for the DRC treatment, feed efficiency was similar ( P = 0.45) because dry matter intake was also greater ( P = 0.04) for DRC when compared with the WSC treatment. Cattle fed DRC also had greater hot carcass weight ( P < 0.01), dressing percentage ( P < 0.01), and Longissimus dorsi muscle area ( P < 0.01) than cattle fed WSC. No differences ( P ≥ 0.18) were observed for marbling score, USDA Yield Grade or USDA Quality Grade. In conclusion, feeding DRC to feedlot cattle improved ADG, hot carcass weight, and Longissimus dorsi muscle area, without affecting feed efficiency or meat quality.